Light Delivery In Turbid Media - Haylock, Thomas (University of Waterloo, 2011)
Light delivery and sample handling systems are essential for any high performance imaging application. The custom design for two such devices with medical imaging applications are presented. The first device, a galvanometer-stage combination, is for general use optical coherence tomography and can be configured to scan over a large range of sample sizes and types. The second device, constructed in parallel, a rotation-linear stage combination, has been carefully designed for a specific imaging task: assessing tumour margins. The design of the two devices is driven by operational requirements and although requirements vary greatly from application to application, there are several common parameters that must be considered for every system. In this thesis, parameters like total scan time, scan resolution, sampling rate, and sample type flexibility are analysed and are some of the primary factors that influence the viability of a system for further development. This work's contribution to medical imaging research is the design of two light delivery systems and an analysis process that can be applied to future iterations of scan systems. The devices are shown to be flexible enough for use in test-bed systems, while providing the necessary functionality to meet the needs of medical histology and pathology. Controlling the light delivery and sample positioning of an imaging device adds important functionality to a scan system and is not a trivial task when high spatial-resolution scan spacing is required. The careful design of an imaging system to meet the unique requirements of the application enables better information and better resulting decision making. Advanced imagery provides new insights and perspectives to everyday scenes. It is these new perspectives that allow for re-evaluation and examination of problems with a fresh eye.
Keywords: Light Delivery; Optical Coherence Tomography; Optomechatronics; Galvanometer; Tumour Margin Assessment; System Design Engineering